Application of nano technology in crop production to enhance resource use efficiency with special reference to soil and water conservation: A review - HATTI, VEERESH; M., RAGHAVENDRA; SINGH, Y. V.; SHARMA, S. K.; HALLI, HANAMANT M.; GOUD, B. R. (Journal of Soil and Water Conservation, 2021)
Nanotechnology may offer keener solutions to current intensive agriculture problems. By the end of the 20th century, the controlled preparation of nanomaterials with desired morphology and size were visualized as smart systems in nutrient and water management. There has been significant interest and scope for using nanotechnology and its products in agriculture to improve the resource use efficiency to curtail the high amount of inorganic fertilizer and pesticides usage and protect soil and environment health by judicious use of these essential agro-inputs especially water and nutrients in different crops on sustainable bases. The nanotechnology applications like carbon nano-tubes for increasing seed germination and establishment, clay nanocomposite in soil water conservation, nanofertilizers as ‘Smart nutrient delivery system’, cellulose nanocrystals or nanofibres as absorbents for water remediation, zerovalent iron nanoparticles, metal oxide nanoparticles as various pollutant degraders are emerging as alternative tool of nanotechnology to improve soil fertility, productivity, and quality of agricultural produces. These nanotechnology applications are being visualized as a game-changer in the field of agriculture to improve input use efficiency, productivity apart from a significant reduction in input cost.